Iron-Bearing Minerals from Soils Developing on Volcanic Materials from Southern Chile. Mineralogical Characterization Supported by Mössbauer Spectroscopy - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Gacitua-Santalices, M; Gacitua-Santalices, M (Sociedad Chilena de la Ciencia del Suelo, 2017)
On this work, the iron oxide mineralogy of Chilean volcanic ashes derived soils have been reviewed, emphasizing on new finding linked to the application of Mössbauer spectroscopy. It has been established that free iron oxide layer contributes with positive variable surface charge to the clay-size soil particle, at soil pH. However, the importance of such contribution seems to depend on the evolutionary stage of the different volcanic soil orders, which defines the crystalline degree of their iron oxide contents. Mössbauer spectroscopy complemented with different physical, chemical and instrumental techniques revealed key aspects of iron oxide mineralogy on these Chilean volcanic soils. For instance, results for Ultisol revealed that the evolution of the soil particle could be followed just analysing the main component of their iron oxide mineralogy; thus, the iron oxide mineralogy change when passing from the volcanic ashes (magnetite), to sand-size magnetic separates (partially-oxidized magnetite), to silt-size (strongly-oxidized magnetite), and finally to clay-size (maghemite) soil samples. Therefore, it would seem that physical weathering of the Ultisol produces smaller and more oxidized particles. On the other hand, the Andisol samples, a young volcanic soil compared to Ultisol, seems to have a constant iron oxide mineralogy among all its different particle size fractions: paramagnetic Fe2+ and Fe3+ species with low crystalline degree, the last one possibly assignable to a ferrihydrite-like mineral. Therefore, on the case of Andisols, it seems that the high contents of organic matter somehow prevent mineral evolution towards higher oxidation and more crystalline levels, in agreement with past studies. © 2017, Sociedad Chilena de la Ciencia del Suelo. All rights reserved.